Effects of various laser treatments on surface characterization and repair bond strength of zirconia-reinforced lithium silicate ceramics - Benli, Merve; Hopur Kılıç, Elif Hacer; Eker Gümüş, Beril; Türkyılmaz, İlser (My University, 2024)
Purpose: To evaluate the effects of two different lasers and their use in combination with hydrofluoric acid (HF) etching on the surface roughness of zirconia-reinforced lithium silicate (ZLS) ceramics and their shear bond strength (SBS) to composite resin. Materials and Methods: The five study groups were as follows: NH = Nd:YAG laser + HF gel; (4) Group E = Er:YAG (erbium: yttrium-aluminum-garnet) laser; and (5) Group EH = Er:YAG laser + HF gel. Surface roughness was assessed using a noncontact profilometer, and SBS tests were conducted with a universal testing machine. Results: The mean SBS values were 16.23 +/- 1.77 MPa for Group H, 17.1 +/- 1.65 MPa for Group N, 16.65 +/- 1.11 MPa for Group NH, 8.08 +/- 1.12 MPa for Group E, and 11.58 +/- 0.82 MPa for Group EH. There were significant differences between groups E and EH (P < .001) but no significant differences (P> .05) among the other groups. Conclusions: Clinicians may prefer Nd:YAG laser or the combination of Nd:YAG and HF to intraorally repair fractured areas. Intl Prosthodont 2024;37.92-94. doi: 10.11607/ijp.7951
Keywords: Dentistry; Oral Surgery; Medicine